Poverty and Social Protection in Bulgaria - Hallaert, Jean-Jacques (IMF Working Papers; Working Paper ;, 2020)
Absolute poverty has dropped markedly in Bulgaria but income inequality has increased substantially in the aftermath of the GFC. This increase is due to a rise in market income inequality that was compounded by a reduction in fiscal redistribution. The redistributive role of direct taxation has declined with the introduction of a flat tax and social spending is relatively low and decreasing (as a share of GDP), is concentrated on a few social risks, and experienced a decline in its redistributive efficiency. The COVID-19 crisis is likely to deepen income inequality, increasing the room for redistributive policies.